Ботанічний сад Вроцлавського університету: враження ботаніка - Bahatska, T.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Author visited the Botanical garden of the Wroclaw University. There were described impressions of the institution visited, systematic collections. The brief history of the Botanical garden is given.